Factor VIII delivery devices in haemophilia A. Barriers and drivers for treatment adherence - Isabel Fernández-Arias; Hae Kyung Kim (Elsevier, 2016)
Introduction and objective: To capture the experience of haemophilia A patients with their devices for coagulation factor reconstitution, the barriers for treatment adherence; and to determine their preferences, presenting a new double-chamber syringe (DCS). Method: A cross- sectional research through a supervised survey and a DCS testing session. Results: Seventy-four (74) patients participated, 50% of them on prophylaxis treatment, and 7 years (median) with their usual treatment (IQR 17.25). In the survey, the DCS received the highest score (75/100, p < 0.001) and it was the most likely to be used in prophylactic treatment (p < 0.001). In the practical testing session (n = 29), 62.1% preferred the DCS, and required 43 seconds as median time (24.5-82) for preparation, vs. 4 minutes (1-15) with their usual treatment (p < 0.001). The favourable opinion of their doctor regarding prophylaxis was very influential on the attitude of participants towards treatment adherence (OR = 1.324, CI 95% = 1.040-1.685, p = 0.023). Conclusions: The DCS was the preferred device, and was likely to encourage prophylaxis.